The Effect of Project Based Learning Model in the Group Investigation in Learning Strategy on Social Attitude Student Subject in USI Pematangsiantar - Fenny Mustika Piliang; Asnewastri Asnewastri (Budapest International Research and Critics University, 2020)
This study analyzes the determine the effect of project based learning model in the Group Investigation and conventional of learning strategy on social attitude student subject in USI Pematangsiantar. Samples are taken by total sampling, namely all semester VI students. The total sample of 60 people are grouped into the experimental group with the project based learning model in the Group Investigation, the experimental group with the Group Investigation learning model, and the control group with the conventional learning model. The research instrument was in the form of an observation sheet on students' social attitudes. This research method is quasi-experimental with data analysis techniques using ANOVA test at a significant level α = 5% with the help of the SPSS 21.0 program. The result of this study found that: Social attitudes of students who are taught with project-based learning in the order of Group Investigation 83.10 ± 4.52 are significantly higher compared to Group Investigation learning 69.80 ± 4.56 and conventional learning 63.15 ± 8 , 20 with (Fcount = 57.005; P = 0.000). Thus, it can be concluded that the project based learning model in the Group Investigation order influences the social attitudes of USI Pematangsiantar students.